Determinants of External Debt: A Panel Data Analysis for Oil & Gas Exporting and Importing Countries - Waheed, Abdul (International Journal of Economics and Financial Issues, 2017)
This study investigates the macroeconomic determinants of external debt in oil & gas exporting and importing countries. The study uses panel data of 12 oil & gas exporting and 12 oil & gas importing countries covering the period 2004-2013. The study identifies eight macroeconomic factors that significantly affect the external debt of oil & gas exporting and importing countries. The major lesson learnt from this study is the importance of avoiding particular generalization for external debt accumulation factors for oil & gas exporting and importing countries. Furthermore, the effect of different macroeconomic factors can be different in these two groups of countries. Keywords: External Debt, Panel Data, Oil & Gas, Exports & Imports JEL Classifications: C13, C33, Q41, F14